Towards a multi-level servitization framework: Conceptualizing ambivalence in manufacturing firms. Issue 3 (5th March 2018) - Lenka, Sambit; Parida, Vinit; Sjödin, David Rönnberg; Wincent, Joakim
Abstract : Purpose: The dominant-view within servitization literature presupposes a progressive transition from product to service orientation. In reality, however, many manufacturing firms maintain both product and service orientations throughout their servitization journey. Using the theoretical lens of organizational ambivalence, the purpose of this paper is to explore the triggers, manifestation and consequences of these conflicting orientations. Design/methodology/approach: A multiple case study method was used to analyze five large manufacturing firms that were engaged in servitization. Semi-structured interviews were conducted with 35 respondents across different functions within these firms. Findings: Servitizing firms experience organizational ambivalence during servitization because of co-existing product and service orientations. This paper provides a framework that identifies the triggers of this ambivalence, its multi-level manifestation and its consequences. These provide implications for explaining why firms struggle to implement servitization strategies due to co-existing product and services orientations. Understanding organizational ambivalence, provides opportunity to manage related challenges and can be vital to successful servitization. Originality/value: Considering the theoretical concept of ambivalence could advance the understanding of the effects and implications of conflicting orientations during servitization in manufacturing firms.